Proposal to Improve the Dyeing Process Applying Preventive Maintenance, SMED and Standardization in an Industrial Dry Cleaner - Sanchez, Sandra (2022)
The textile industry is important in the world economy and is one of the most influential sectors with a turnover of $2.6 billion. In 2019, national production grew 1.12% and manufacturing GDP 3.5%. This industry has an 18.8% increase in exports and generates more than 250 thousand jobs. It has experienced various changes in recent years that influence the dry-cleaning industry, such as modern advances with the need to provide quality and in search of optimal production efficiency. For this reason, the use of methodologies for continuous improvement has become an important consideration in companies. The case study presents an efficiency of 66%, due to unproductive times due to machine stops and additional times due to reprocessing in the dyeing area. In this article, an improvement model will be proposed, which will consist of the implementation of Preventive Maintenance, SMED and Operations Standardization tools, and then integrate them through PDCA. The contribution is the combination of the three tools, which has not been done in scientific articles. Finally, after the implementation, it is expected to reach an efficiency of 85.95%.